Knowledge and experience of physicians during the COVID-19 Pandemic: A global cross-sectional study. - Rania Mansour; Smrithi Rallapalli; Hamreet Kaur Baidwan; Mohammad S Razai; Linda Abou-Abbas (Public Library of Science (PLoS), 2022)
Physicians are on the frontline of the COVID-19 pandemic with responsibility to manage the disease. The aim of this study is to investigate physicians' knowledge, attitudes, perceptions and experiences, as well as preventative practices regarding the COVID-19 pandemic and COVID-19 vaccinations. Further, we explore physicians' recommendations for future pandemics. A mixed-methods online survey was disseminated to physicians globally. The survey was distributed via social media from August 9-30, 2021. Data collected included sociodemographic characteristics, knowledge, attitudes, and practices towards COVID-19, concerns regarding vaccinations, and perspectives on policies implemented. Descriptive statistics were reported, and qualitative data were analysed using inductive thematic analysis. A total of 399 physicians from 62 countries completed the survey, with similar participation from High Income Countries and Low- or Middle-Income Countries. Most physicians (87%) revealed a good level of knowledge while only half (54%) reported adhering to adequate preventative measures. More than half of participants (56%) indicated that the policies implemented to handle COVID-19 by their public health agencies were insufficient or disorganised. While most physicians reported increased mental stress (61%) and described their experience with COVID-19 using negative terminology (63%), most physicians (87%) indicated they are willing to continue working in healthcare. Physicians globally possessed good knowledge of COVID-19 and COVID-19 vaccinations; yet improvements in ensuring compliance with preventative measures is warranted. Findings from this study have important implications. As recommended by physicians, efforts to manage pandemics should involve (1) strengthening health systems, (2) minimising adverse effects of infodemics, (3) delegating decision-making roles appropriately, and (4) acknowledging global responsibility.